2022
DOI: 10.3389/fped.2022.920840
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted design model to evaluate the outcome of combined osteotomies in Legg-Calvé-Perthes disease

Abstract: ObjectiveThe current study aims to conduct a quantitative dynamic analysis of hip morphology using a computer-assisted design (CAD) model to evaluate the combined pelvic and femoral osteotomies in the treatment of Legg-Calvé-Perthes disease (LCPD).Materials and methodsCAD models of patients with unilateral LCPD treated by combined pelvic and proximal femoral osteotomies were established based on the data of CT scan, on which morphological parameters were measured. Shape difference analysis of normal hips was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The bone reconstruction model of 3D CT provides an omnidirectional and multiangle observation index for clinicians to observe the pathological changes of the hip joint and the curative effect of surgery, and has value for guiding surgical planning and prediction of postoperative acetabular shape[ 28 ]. Li et al [ 29 ] used computer-aided design for quantitative dynamic analysis of hip joint morphology, and found that it was a better guide for surgical planning and evaluation of treatment results. Some clinical studies have found that the value and safety of using 3D CT to guide pelvic osteotomy is higher than that of ordinary CT[ 30 ].…”
Section: Evaluation Of Acetabular Morphology By Computed Tomographymentioning
confidence: 99%
“…The bone reconstruction model of 3D CT provides an omnidirectional and multiangle observation index for clinicians to observe the pathological changes of the hip joint and the curative effect of surgery, and has value for guiding surgical planning and prediction of postoperative acetabular shape[ 28 ]. Li et al [ 29 ] used computer-aided design for quantitative dynamic analysis of hip joint morphology, and found that it was a better guide for surgical planning and evaluation of treatment results. Some clinical studies have found that the value and safety of using 3D CT to guide pelvic osteotomy is higher than that of ordinary CT[ 30 ].…”
Section: Evaluation Of Acetabular Morphology By Computed Tomographymentioning
confidence: 99%